The Street to the Highway: The Unspoken Secrets Behind Converting Small Businesses Into Large Companies - Bajpai, Vineet (Bengaluru: c)
This book shatters the myth that corporate success is a matter of destiny for a few chosen business barons. It shows that business growth is not the result of some supernormal capabilities of a few super-individuals but is an outcome of a systematic and well planned construct of strategies and actions. Written in an uncomplicated style this book would appeal to corporate managers, students, academia, young executives, entrepreneurs, CEOs and most of all to millions of small business owners. A must read for every entrepreneur, every business leader and every employee of a small or mid-sized company.